Analysis of the Teams Games Tournament (TGT) Method in Microteaching for Teaching the Topic of Faith in Angels in the Generation Z Era - Haniefah Iqtianti; Isti Koma; Fidari Nur Dini; Citra Ayu Hidayah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research aims to analyze the implementation of the Team Games Tournament (TGT) method in microteaching for the material of Faith in Angels to address the learning characteristics of Generation Z. In the digital era, the primary challenge in Islamic Education (PAI) is transforming abstract theological topics into interactive and relevant lessons for students. The research method used is descriptive qualitative, focusing on pre-service PAI teacher students in microteaching courses. Data collection techniques included observation of teaching simulations, in-depth interviews, and analysis of lesson plan documents (RPP). The results indicate that the TGT method increases active engagement among students, transforms the classroom atmosphere into a more dynamic one through healthy competition, and facilitates the visualization of angels' duties in daily life through academic games. These findings confirm that game-based cooperative learning strategies are highly effective in meeting the psychological needs of Generation Z, who favor challenges and immediate feedback, while simultaneously strengthening spiritual understanding in the era of disruption.